2010
DOI: 10.1111/j.1365-2818.2010.03447.x
|View full text |Cite
|
Sign up to set email alerts
|

The saucor, a new stereological tool for analysing the spatial distributions of cells, exemplified by human neocortical neurons and glial cells

Abstract: Summary The 3D spatial arrangement of particles or cells, for example glial cells, with respect to other particles or cells, for example neurons, can be characterized by the radial number density function, which expresses the number density of so‐called ‘secondary’ particles as a function of their distance to a ‘primary’ particle. The present paper introduces a new stereological method, the saucor, for estimating the radial number density using thick isotropic uniform random or vertical uniform random sections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…A quarter of a century has passed since the milestone that marked the generation of the so-called 'design-based' generation of stereological methods (Sterio, 1984). These continue to be updated, with the advent of new tools Gardi et al 2008;Stark et al 2011) and applications in different fields of knowledge, with a traditionally special emphasis to neurosciences (Mayhew & Gundersen, 1996;Mouton, 2002). Nowadays, this generation of methods coexists with the old 'model-based' strategies, but differences exist between the methodologies: the 'design-based' approach implies that no strict assumptions (about shape, size, orientation or distribution) are made about the objects under study and, instead, that a system of sampling rules is designed in order to ensure that all objects in the targeted space have the same probability of being sampled and targeted by the desired probe (Geuna, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A quarter of a century has passed since the milestone that marked the generation of the so-called 'design-based' generation of stereological methods (Sterio, 1984). These continue to be updated, with the advent of new tools Gardi et al 2008;Stark et al 2011) and applications in different fields of knowledge, with a traditionally special emphasis to neurosciences (Mayhew & Gundersen, 1996;Mouton, 2002). Nowadays, this generation of methods coexists with the old 'model-based' strategies, but differences exist between the methodologies: the 'design-based' approach implies that no strict assumptions (about shape, size, orientation or distribution) are made about the objects under study and, instead, that a system of sampling rules is designed in order to ensure that all objects in the targeted space have the same probability of being sampled and targeted by the desired probe (Geuna, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…1988; Gardi et al. 2008; Stark et al. 2011) and applications in different fields of knowledge, with a traditionally special emphasis to neurosciences (Mayhew & Gundersen, 1996; Mouton, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…These indices assess the level of infection in tissues and can reveal differences between individuals subjected to specific treatments or that exhibit different levels of resistance or susceptibility to the pathogen. An alternative method for quantifying the level of tissue infection and colonisation by pathogens includes a combination of microscopic techniques and digital analysis of images, and includes the application of stereological techniques in microscopy [ 28 , 29 ]. The use of stereological techniques in histological analysis requires the use of many equations and specialized statistical processing, which entails a highly specialized staff and a substantial investment of time and resources [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“… 6 Another study used the saucer method and also indicated that spatial arrangement of glial cells around neurons was different in various subregions of the human neocortex. 7 The alterations in the spatial arrangement of the glial cells and the neurons may reflect functional changes in the relationship between them. 8 , 9 , 10 Therefore, at the first step, the present study aims to evaluate the spatial arrangement of the neurons and glial cells as well as their relationship after stress in rats.…”
Section: Introductionmentioning
confidence: 99%